ABC of eyes - Khaw, Peng Tee; Elkigton, A R (London: BMJ Books, 1991)
ABC of Eyes is a practical and concise guide to common eye conditions, designed primarily for general practitioners, medical students, and primary care providers. It presents clear explanations of eye anatomy, examination techniques, and the recognition and management of frequently encountered disorders such as conjunctivitis, cataract, glaucoma, age-related macular degeneration, and diabetic retinopathy. The book emphasizes early diagnosis, appropriate referral, and basic treatment principles, using illustrations and clinical photographs to support learning. Its straightforward, case-based approach makes it a useful resource for improving confidence in assessing eye complaints in everyday clinical practice.
DC010226
In english.
Keywords: Khaw, Peng Tee; Eye -- Diseases; Ophthalmology. -- Examination; Eye; Eye - - -- Diseases. -- Diagnosis; Eye -- Diseases; Eye Diseases -- diagnosis; Eye -- Diseases -- Therapy; Ophthalmology -- Handbooks, -- manuals, etc; Eye - -- Diseases -- Treatment